Introduction and Characteristics of SARS-CoV-2 in North-East of Romania During the First COVID-19 Outbreak - Lobiuc, Andrei; Dimian, Mihai; Gheorghita, Roxana; Sturdza, Olga Adriana Caliman; Covasa, Mihai (Frontiers in Microbiology, 2021)
Romania officially declared its first SARS-CoV-2 case on February 26, 2020. The first and largest COVID-19 outbreak in Romania was recorded in Suceava, North-East region of the country, and originated at the Suceava regional county hospital. Following sheltering-in-place measures, infection rates decreased, only to rise again after relaxation of measures. This study describes the incursion of SARS-CoV-2 in Suceava and other parts of Romania and analyses the mutations and their association with clinical manifestation of the disease during the period of COVID-19 outbreak. Sixty-two samples were sequenced via high-throughput platform and screened for variants. For selected mutations, putative biological significance was assessed, and their effects on disease severity. Phylogenetic analysis was conducted on Romanian genomes (n=112) and on sequences originating from Europe, UK, Africa, Asia, South and North America (n=876). The results indicated multiple introduction events for SARS-CoV-2 in Suceava, mainly from Italy, Spain, UK and Russia although some sequences were also related to those from the Czech Republic, Belgium and France. Most Suceava genomes contained mutations common to European lineages, such as A20268G, however approximately 10% of samples were missing such mutations, indicating a possible different arrival route. While overall genome regions ORF1ab, S and ORF7 were subject to most mutations, several recurring mutations such as A105V were identified, and these were mainly present in severe forms of the disease. Non-synonymous mutations, such as T987N (Thr987Asn in NSP3a domain), associated with changes in a protein responsible for decreasing viral tethering in human host were also present. Patients with diabetes and hypertension exhibited higher risk ratios of acquiring severe forms of the disease and these were mainly related to A105V mutation. This study identified the arrival routes of SARS-CoV-2 in Romania and revealed potential associations between the SARS-CoV-2 genomic organization circulating in the country and the clinical manifestation of COVID-19 disease.